Management of diabetes and associated costs in a complex humanitarian setting in the Democratic Republic of Congo: a retrospective cohort study - David Prieto-Merino; Pablo Perel; Bayard Roberts; Éimhín Mary Ansbro; Michel Biringanine; Grazia Caleo; Zia Sadique; Kiran Jobanputra (BMJ Open)
Objective We aimed to evaluate an Integrated Diabetic Clinic within a Hospital Outpatient Department (IDC-OPD) in a complex humanitarian setting in North Kivu, Democratic Republic of Congo. Specific objectives were to: (1) analyse diabetes intermediate clinical and programmatic outcomes (blood pressure (BP)/glycaemic control, visit volume and frequency); (2) explore the association of key insecurity and related programmatic events with these outcomes; and (3) describe incremental IDC-OPD programme costs.Design Retrospective cohort analysis of routine programmatic data collected from January 2014 to February 2017; analysis of programme costs for 2014/2015.Setting Outpatient diabetes programme in Mweso hospital, supported by Médecins sans Frontières, in North Kivu, Demographic Republic of Congo.Participants Diabetes patients attending IDC-OPD.Outcome measures Intermediate clinical and programmatic outcome trends (BP/ glycaemic control; visit volume/frequency); incremental programme costs.Results Of 243 diabetes patients, 44.6% were women, median age was 45 (IQR 32–56); 51.4% were classified type 2. On introduction of IDC-OPD, glucose control improved and patient volume and visit interval increased. During insecurity, control rates were initially maintained by a nurse-provided, scaled-back service, while patient volume and visit interval decreased. Following service suspension due to drug stock-outs, patients were less likely to achieve control, improving on service resumption. Total costs decreased 16% from 2014 (€36 573) to 2015 (€30 861). Annual cost per patient dropped from €475 in 2014 to €214 in 2015 due to reduced supply costs and increased patient numbers.Conclusions In a chronic conflict setting, we documented that control of diabetes intermediate outcomes was achievable during stable periods. During insecure periods, a simplified, nurse-led model maintained control rates until drug stock-outs occurred. Incremental per patient annual costs were lower than chronic HIV care costs in low-income settings. Future operational research should define a simplified diabetes care package including emergency preparedness.